International Conference on Information Technology and Communication Systems (Advances in Intelligent Systems and Computing,, 2018)
This book reports on advanced methods and theories in two related fields of research, Information Technology and Communication Systems. It provides professors, scientists, PhD students and engineers with a readily available guide to various approaches in Engineering Science. The book is divided into two major sections, the first of which covers Information Technology topics, including E-Learning, E-Government (egov), Data Mining, Text Mining, Ontologies, Semantic Similarity Databases, Multimedia Information Processing, and Applications. The second section addresses Communication Systems topics, including: Systems, Wireless and Network Computing, Software Security and Monitoring, Modern Antennas, and Smart Grids. The book gathers contributions presented at the International Conference on Information Technology and Communication Systems (ITCS 2017) held at the National School of Applied Sciences of Khouribga, Hassan 1st University, Morocco on March 28-29, 2017. This event was organized with the objective of bringing together researchers, developers, and practitioners from academia and industry working in all areas of Information Technology and Communication Systems. It not only highlights new methods, but also promotes collaborations between different communities working on related topics.